The Relationship Between Work Motivation and Optimism Towards Adversity Quotient in Honorary Teachers in Tanjung Balai City - Rahmah Khair, Muna; Hasanuddin, Hasanuddin; Hardjo, Suryani (Lafadz Jaya Publisher, 2024)
Empirically, this study aims to examine the relationship between Work Motivation and Optimism on the Adversity Quotient in Honorary Teachers. The population of this study consisted of 500 teachers, with a sample of 125 teachers selected through random sampling. Data collection techniques included questionnaires and documentation, while data analysis was conducted using regression and ANOVA tests. The results of this study show that Work Motivation and Optimism positively influence the Adversity Quotient. Based on the analysis, it was found that the Work Motivation variable (x1) influences the emergence of the Adversity Quotient (t = 34.181), while the Optimism variable (x2) does not significantly influence the emergence of the Adversity Quotient (t = 1.493). The combined influence of Work Motivation and Optimism on the emergence of the Adversity Quotient is 93.9%. The significance value for the simultaneous influence of X1 and X2 on Y is 0.000 < 0.05, and the calculated F value is 913.956 > F table value of 3.07.